2020
DOI: 10.5552/drvind.2020.1916
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Fiber Reinforced Polymer-Based Wood Composites Used in Furniture Construction Considering Semi-Rigid Connections

Abstract: In this study, control samples of pine (Pinus slyvestris L.), beech (Fagus orientalis L.) and oak (Quercus petreae L.) species were obtained by using fi ber reinforced finger corner joints. Teknobont 200 epoxy and polyvinyl (PVAc) adhesives were used as glue. Bearing in mind the critical loads that may affect their use, experimental samples were tested under diagonal loads. Experimental samples were also analyzed by a computer program using the finite element method (FEM). Finally, experimental data were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Hu and Liu (2020) compared three types of M&T joint finite element models, which confirmed that the semirigid model performed better to simulate the bending strength of wood joints. Zor and Kartal (2020) further verified the validity of using a semi-rigid joint model in simulating furniture corner joints via FEM. Kaygin et al (2016) tested the diagonal compression and tension of corner joints based on simulation and experimental methods, which were carried out using dowel and M&T elements.…”
Section: Introductionmentioning
confidence: 59%
“…Hu and Liu (2020) compared three types of M&T joint finite element models, which confirmed that the semirigid model performed better to simulate the bending strength of wood joints. Zor and Kartal (2020) further verified the validity of using a semi-rigid joint model in simulating furniture corner joints via FEM. Kaygin et al (2016) tested the diagonal compression and tension of corner joints based on simulation and experimental methods, which were carried out using dowel and M&T elements.…”
Section: Introductionmentioning
confidence: 59%
“…This is mostly because the support conditions and element connections are far from ideal in most cases [1]. Bridges [2], multistorey buildings [3], truss and precast structures [4,5], aircraft wings [6], wearable structures [7], furniture construction [8] are among many others that detailed analysis is carried out using R/PFs while also proving that these connections have a big impact on the overall structural behavior [9,10]. In this context, R/PFs have also been an important element of various structural design [11,12,13,14] and structural optimization [15,16,17,18] studies.…”
Section: Introductionmentioning
confidence: 99%